2006
DOI: 10.1007/s10886-006-9071-6
|View full text |Cite
|
Sign up to set email alerts
|

Kairomonal Response of Predators to Three Pine Bast Scale Sex Pheromones

Abstract: The kairomonal activity of the sex pheromones of three pine bast scales, Matsucoccus feytaudi, Matsucoccus josephi, and Matsucoccus matsumurae, as well as a new analog of the M. feytaudi sex pheromone, were investigated in pine forests of France, Portugal, and Italy. The response of the maritime pine bast scale predators, Elatophilus spp. and Hemerobius stigma, was used to test the influence of trapping methods, kairomone composition, and dose. Both predators showed significant attraction to all compounds exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
1
16
0
2
Order By: Relevance
“…Previous field tests with the pityolure also showed higher pheromone-trap captures with 2 mg than 1 mg (Einhorn et al, 1983) or with 1 mg compared to 0.0005 mg (Cuevas et al, 1983a). However, our data further demonstrate an asymptotic pheromone dose-response that seems to be quite common among insects (Hibbard et al, 1991;Evenden et al, 1995;Knutson et al, 1998;Rao and Subbaratnam, 1998;Branco et al, 2006a) and can partly be explained by an increase in the sampling area with increased dosage (Branco et al, 2006b). The rapid initial increase of male response to pheromone dosage followed by a more constant number of captures suggests a saturation level around 10 mg and no overdose repellence effect.…”
Section: Development Of the Pheromone-baited Trapsupporting
confidence: 57%
“…Previous field tests with the pityolure also showed higher pheromone-trap captures with 2 mg than 1 mg (Einhorn et al, 1983) or with 1 mg compared to 0.0005 mg (Cuevas et al, 1983a). However, our data further demonstrate an asymptotic pheromone dose-response that seems to be quite common among insects (Hibbard et al, 1991;Evenden et al, 1995;Knutson et al, 1998;Rao and Subbaratnam, 1998;Branco et al, 2006a) and can partly be explained by an increase in the sampling area with increased dosage (Branco et al, 2006b). The rapid initial increase of male response to pheromone dosage followed by a more constant number of captures suggests a saturation level around 10 mg and no overdose repellence effect.…”
Section: Development Of the Pheromone-baited Trapsupporting
confidence: 57%
“…Ranges of values are given for the area colonised by 2011. In a previous study, we found that the pheromone release threshold triggering the attraction of E. nigricornis (a kairomonal effect) was much higher than that for the attraction of M. feytaudi males (Branco et al 2006). Correlation coefficients (Pearson's r) indicate the direction of individual explanatory variable effects on the spread of the invasion.…”
Section: Inference Of Spread Rate and Wind Dispersalmentioning
confidence: 95%
“…La localización de sus presas a través de sus secreciones, kairomonas, alomonas y/o feromonas ha sido frecuentemente registrada, y sobre ellas pueden llegar a ser extremadamente voraces (Withycombe, 1925;Principi, 1954bPrincipi, , 1984Tjeder, 1966;Canard, 1973aCanard, , 1973bWattebled et al, 1978;Samson & Blood, 1979Canard & Duelli, 1984;New, 1986aNew, , 1988aNew, , 1989New, , 2001Duelli, 1987b;Frazer, 1988;Szentkirályi, 1989Szentkirályi, , 2001aMcEwen et al, 1993aMcEwen et al, , 2001Růžička, 1994Růžička, , 1997aRůžička, , 1997bRůžička, , 1998Růžička, , 2010Mendel et al, 1997Mendel et al, , 2004Boo et al, 1998Boo et al, , 1999Boo et al, , 2003Bakthavatsalam & Singh, 1999;Nelson et al, 2001;Canard & Volkovich, 2001;Penny, 2002;Branco et al, 2006aBranco et al, , 2006bSchwartzberg et al, 2008;Koczor et al, 2010Koczor et al, , 2015.…”
Section: Datos Generales Sobre Su Biología Comportamiento Estadios unclassified